Programa Aqui tem Farmácia Popular e o direito fundamental à saúde : uma nova proposta de fiscalização das fraudes pelo Ministério Público Federal - Rocha, Marcelo Dantas (2018)
In the Brazilian Constitution the Right to Health is a fundamental right of every human being, to be provided in a comprehensive and universally way. The access to medicines is fundamental to accomplish this. Since 1998, the Brazil’s National Medicines Policy is being reinforced, for example, by regulating generic drugs, encouraging pharmaceutical assistance and launching the Brazilian Popular Pharmacy Program (Aqui Tem Farmácia Popular, in Portuguese). The latter attends around 10 million people and has partnership with more than 32 million drugstores. But corruption is weakening programs like this, affecting not only policies related to healthcare but other ones important in guaranteeing human rights. In ATFP’s case it steps back from social gains once achieved and burdens family budgets, contributing to higher mortality and hospital expenses. Therefore, this work analyzes how to improve the Brazilian Public Ministry’s (MPF, acronym in Portuguese) trials in relation to these misappropriations of funds, especially on improbity and fraud. This work proposes an alternative method that intends to be faster and standardized. It elected the research line titled “Legal Aspects in the Public Sector”, under guidance of the Legal and Economic Sciences Department, from the Federal University of Espirito Santo. It is inner circumscribed in the Postgraduate Program in Public Management. Its methodology is mainly qualitative, based on secondary data - such as these from essays and thesis – and documentary, for instance the procedures of MPF and public databases.